2009
DOI: 10.1063/1.3096987
|View full text |Cite
|
Sign up to set email alerts
|

Twist grain boundaries in cubic surfactant phases

Abstract: Twist grain boundaries in bicontinuous cubic surfactant phases are studied by employing a Ginzburg-Landau model of ternary amphiphilic systems. Calculations are performed on a discrete real-space lattice with periodic boundary conditions for the lamellar L ␣ , gyroid G, diamond D, and the Schwarz P phases for various twist angles. An isosurface analysis of the scalar order parameter reveals the structure of the surfactant monolayer at the interfaces between the oil-rich and water-rich regions. The curvature di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…Note that the deviations are only prominent in the vicinity of the twin boundary and decay fast within a short distance. In fact, a similar decay has also been reported for a simulated twist grain boundary in LLC within the Ginzburg-Landau scheme (Belushkin & Gompper, 2009).…”
Section: Numerical Modelling Of Minimal and Cmc Twinssupporting
confidence: 79%
See 1 more Smart Citation
“…Note that the deviations are only prominent in the vicinity of the twin boundary and decay fast within a short distance. In fact, a similar decay has also been reported for a simulated twist grain boundary in LLC within the Ginzburg-Landau scheme (Belushkin & Gompper, 2009).…”
Section: Numerical Modelling Of Minimal and Cmc Twinssupporting
confidence: 79%
“…Note that the deviations are only prominent in the vicinity of the twin boundary and decay fast within a short distance. In fact, a similar decay has also been reported for a simulated twist grain boundary in LLC within the Ginzburg-Landau scheme (Belushkin & Gompper, 2009). It is interesting to note that the opposite sides of the partitioning layer can be asymmetric, hence one side can be more strongly perturbed by twinning than the other.…”
Section: Numerical Modelling Of Minimal and Cmc Twinssupporting
confidence: 76%
“…Here, we develop and use a technique based on surface reconstruction (SI Text), which closely follows the one successfully applied to study amphiphilic systems (43). More specifically, we construct a surface enveloping the arms of the gel.…”
Section: Resultsmentioning
confidence: 99%
“…This was similar to surfactant systems in bulk, in which Belushkin et. al [33] found with a Ginzburg-Landau model that the grain boundary between two orthogonal lamellar grains was a good approximation of a minimal surface and was well described by the Scherk's first surface. Thus, our simulations showed that the formation of the interface between domains resulted in a bicontinuous and double-periodic structure.…”
Section: Figmentioning
confidence: 97%